The Effect Of Work From Home (WFH) On Company Employee Performance in Bandung City - Putri, Fida Ayu Nurrizkia; Fadlhurrohman, Fakhri Jubair; Pratama, Fauzan Mupti (JURNAL ADMINISTRASI KANTOR, 2023)
The WFH system has been proven to really help employees' work during the Covid-19 pandemic. However, even though the pandemic is over, the WFH system is still being implemented in many companies in Indonesia and even in companies abroad. Therefore, this research aims to determine the factors that influence employee productivity, the relationship between WFH factors and employee productivity, and the impact that the WFH system has on employee productivity in the post-Covid-19 pandemic. This research is quantitative research using a questionnaire distribution method. The population in this study were company employees in Bandung City. This research uses data analysis methods with the help of the IBM SPSS Statistics software application in its process. From the research results that have been obtained, it can be concluded that WFH / Work From Home has an effect on employee performance. The freedom of working time provided by WFH can increase freedom and balance between personal and professional life. Without having to travel to the office, employees can save time and energy, reduce stress, and focus on work tasks. Technology solutions that support virtual communications are critical to bridging this gap. Management's role is also key, with the need for clear guidance, support and effective performance monitoring. The Work From Home (WFH) system has a complex impact on employee performance, such as social interaction and team collaboration can also hinder, affecting innovation and the effectiveness of working together.   Keywords : WFH, Employee Performance, Company Systems.